Comparative Analysis of the Effect Of Blended Learning Model Through Experimental Approach and Project on the Scientific Demeanor and Learning Outcomes - Fitri Wardani (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper analyzes differences in students’ learning outcomes in a blended learning model that uses experimental and project methods. In addition, this paper also investigates the effect of scientific demeanor on learning outcomes. The research method uses a simple random sampling technique in four classes at the Light Vehicle Engineering department. The research uses four variables, namely scientific demeanor, learning outcomes, physics learning that uses a blended learning model with experimental, and project methods. Scientific attitude is observed through observing participants' responses to specific situations while learning outcomes are measured through tests that are taken after a particular learning process. The research results indicate three main findings. First, there are significant differences in learning outcomes between students who are taught by using the blended learning model with the experimental method and the students who are taught with the project method. Second, there are substantial differences in learning outcomes based on students' scientific demeanor. Third, there is no significant effect between the blended learning model using experimental and project methods and students' demeanor toward learning outcomes. The research results contribute to the understanding of how different learning can influence students’ learning outcomes. In addition, the findings regarding the relationship between scientific demeanor and learning outcomes can also support efforts to develop more effective and adaptive learning strategies for various types of students.